Investigation on the crystallization behavior and morphology of β-nucleated isotactic polypropylene/glass fiber composites. Issue 3 (3rd July 2017) - Zeng, Fangxinyu; Peng, Hongmei; Chen, Jinyao; Kang, Jian; Yang, Feng; Cao, Ya; Xiang, Ming
ABSTRACT: The isotactic polypropylene (iPP) with different uniformities of stereo-defect distribution was synthesized, and the β-nucleated iPP/glass fiber composites (TPPA-GF and TPPB-GF) were prepared. The influence of glass fiber on the non-isothermal crystallization kinetics, β-phase crystallization, and morphology behavior of the composites were investigated by means of differential scanning calorimetry (DSC), scanning electronic microscopy (SEM), and wide angle X-ray diffraction (WAXD). The results revealed that for both TPPA-GF and TPPB-GF, as the amount of GF increases, the crystallization peak temperature and relative degree of crystallinity increase gradually, while crystallization peak width decreases gradually. Meanwhile, the half crystallization time t1/2 of both TPPA and TPPB decreases gradually, indicating that the addition of GF can accelerate the crystallization of both TPP-A and TPP-B. Moreover, the addition of glass fiber decreases the energy barriers ΔE and makes the composites to crystallize easier. The results of melting behavior study and WAXD indicate that high cooling rate leads to relatively low crystallization temperature and low thermal stability, resulting in higher β-phase content with relatively low thermal stability, while low cooling rate leads to high crystallization temperature and high thermal stability, which is more favorable for the formation of less amount of β-phase with high thermal stability. For both TPPA and TPPB, the higher the content of glass fiber, the lower the βc . The addition of glass fiber not only reduces the content of β-phase but also destroys its spherulite morphology. It was also observed that the glass fiber is more uniformly dispersed in TPPB compared with TPPA.